Diurnal Regulation of Peripheral Glucose Metabolism: Potential Effects of Exercise Timing. (31st May 2020) - Mancilla, Rodrigo; Krook, Anna; Schrauwen, Patrick; Hesselink, Matthijs K. C.
Abstract : Diurnal oscillations in energy metabolism are linked to the activity of biological clocks and contribute to whole‐body glucose homeostasis. Postprandially, skeletal muscle takes up approximately 80% of circulatory glucose and hence is a key organ in maintenance of glucose homeostasis. Dysregulation of molecular clock components in skeletal muscle disrupts whole‐body glucose homeostasis. Next to light‐dark cycles, nonphotic cues such as nutrient intake and physical activity are also potent cues to (re)set (dys)regulated clocks. Physical exercise is one of the most potent ways to improve myocellular insulin sensitivity. Given the role of the biological clock in glucose homeostasis and the power of exercise to improve insulin sensitivity, one can hypothesize that there might be an optimal time for exercise to maximally improve insulin sensitivity and glucose homeostasis. In this review, we aim to summarize the available information related to the interaction of diurnal rhythm, glucose homeostasis, and physical exercise as a nonphotic cue to correct dysregulation of human glucose metabolism.